Apocynaceae of continental South-East Asia: new species, new records and new combinations - Rodda, Michele; Armstrong, Kate; Klackenberg, Jens (Thai Forest Bulletin (Botany), 2024)
This paper makes necessary taxonomic and nomenclatural adjustments prior to publication of accounts of Apocynaceae (Asclepiadoideae, Periplocoideae, Secamonoideae) for the Floras of Thailand, Peninsular Malaysia, and Cambodia, Laos and Vietnam. It includes the publication of two new species, Gymnemopsis krabiensis and Gymnemopsis thailandica; new country records of Dolichopetalum kwangsiense, Dischidia antennifera, Gongreos curtisii and Vincetoxicum cissoides for Thailand and of Gongronema napalense for both Thailand and Myanmar; two new combinations in Gongreos; 10 new combinations and four new names in Secamone; three new combinations in Stephanotis; one new combination in Pseudosarcolobus; and 11 typifications.